Converting the Functional Independence Measures (FIM)-motor Scores to Modified Barthel Index (MBI) Scores —A Data Mining Approach - WONG Lik-hang Gary; WONG Kam-man Simon; NG Hin-Po Bobby (康复学报)
ObjectiveTo meet both clinical and research needs, this study developed and evaluated a conversion method between the Modified Barthel Index (MBI) and the Functional Independence Measures (FIM).MethodsThis was a retrospective analysis of both MBI & FIM assessment data, which were collected concurrently in a local hospital for stroke patients attending rehabilitation programs in the period from 2005 to 2016. The scorings were rated at the beginning of the rehabilitation. Data mining procedures, which involved the following steps: a) selection of appropriate samples, b) pre-processing of the dataset, c) transformation of the dataset, d) analyzing the data patterns, e) deriving the conversion based on "rank-invariant statistical method", and, f) verifying the conversion method — were adopted for data analysis.ResultsSix thousand five hundred and seventy-four cases, which were verified as "error-free", were randomly allocated into two compatible subsets. Using the data from subset (A), we substantiated that all the total scores and every corresponding paired item scores between the MBI and the FIM-motor were highly correlated (i.e. Kendall's tau-b Value ranged from 0.796 to 0.987, P<0.01). Based on "rank-invariant statistical method" an item-to-item conversion table was also developed. Using the data from subset (B) we found the Cohen's Kappa coefficients (k) for either "single-pair" items or "multiple-pair" items ranged from 0.770 to 0.913 — which indicated "substantial" to "almost perfect" agreement between the rated MBI scores and the derived MBI scores.ConclusionA "user-friendly" and yet methodologically sound conversion method is recommended for application in stroke rehabilitation program.